Evaluation of Supply Chain Planning by Currency Control Bodies in the Russian Federation - Svetlana V. Krivoshapova; Irina A. Samsonova; Ilya A. Bedrachuk (International Journal of Supply Chain Management, 2019)
The article determines the effectiveness of currency control body activities in the Russian Federation by supply chain management. Currency regulation and currency control, the methodology of international calculations for export-import transactions is one of financial policy trends in the Russian Federation. The instruments of currency regulation and currency control affect the balance of payments, the rate of national currency, the level of foreign exchange reserves, provide the necessary dynamics of foreign trade development. The main problem in this case is the issue of balancing the freedom of foreign economic activity and government control over its subjects. In such conditions, the role of currency regulation and currency control increases sharply in the state. It should be noted that, despite the increase of imposed penalty collection and the increase of currency control body work efficiency, one cannot say that currency control was ineffective in 2015-2017. Ideally, the effectiveness of control activities should be reflected in violations and imposed penalties volume reduction, which in turn would mean the control effectiveness increase. Let's note that the identification of suspicious transactions should be carried out at the banking level; therefore, their elimination can be achieved only through the effective work of currency control agents.